Modulation of the progesterone receptor by progestogens, antiretroviral drugs and the glucocorticoid receptor - Enfield, Kim (Department of Molecular and Cell Biology, 2022)
Hormonal contraceptives (HCs) and hormonal replacement therapies (HRTs) are widely used globally by women. However, the relative activity of some of the progestogens used in HCs and HRT has not been determined via their target steroid receptor (SR), the progesterone receptors and its isoforms (PR-A and PR-B). This thesis involves an in vitro investigation of some of the factors that affect PR activity and that may thus impact progestogen responses in women on HC or HRT. These include progestogen-specific effects via PR-A and PR-B, progestogen metabolism, the role of antiretroviral drugs (ARVs) and crosstalk with the glucocorticoid receptor (GR). The PR isoforms play important roles in multiple physiological processes, including cognition, regulation of inflammation, mitochondrial function, neurogenesis, female reproduction and disease. Due to the gender disparity of higher prevalence of HIV infection among women compared to same-aged men, there is increased interest in developing treatments designed to protect women from HIV infection. These include HIV pre-exposure prophylactics (PrEPs) and multipurpose prevention technologies (MPTs). Furthermore, many HIV -infected women are using combined antiretroviral therapy (cART) to treat AIDS as well as an HC to prevent unwanted pregnancy. Importantly, the effects of the combination of a progestogen with ARVs on the activity of the PR is unexplored. In addition, there are many studies which provide evidence that SRs interact and influence each other's activity. Therefore, the presence of the ubiquitously GR may also influence PR activity. To characterise the progestogen-induced activity of the PRs, dose-response analysis was performed using promoter-reporter genes and varying doses of progesterone (P4) and five widely-used progestogens namely; norethisterone (NET), etonogestrel (ETG), levonorgestrel (LNG), medroxyprogesterone acetate (MPA) and nestorone (NES), in parallel relative to the reference progestogen promegestone (R5020). The effects of experimental conditions and progestogen metabolism on PR activity were investigated in U2OS cells using two different transient transfection conditions to express PR-B. The effect of model system on PR activity was investigated by comparing the progestogen-induced PR-B responses obtained in U2OS cells to those obtained in MDA-MB-231 cells stably transfected with expression vectors for PR-A or PR-B. Progestogen-induced PR activity was also investigated on endogenous genes by quantitative real-time PCR (real-time qPCR) in the MDA-MB-231 PR-B-stably expressing (MDA-PR-B+) cells. Once the progestogen responses via the PR were characterised, PR-B activity in the presence of three ARVs namely; tenofovir disoproxil fumarate (TDF), dapivirine (DPV) and maraviroc (MVC), was investigated next using promoter-reporter assays and real-time qPCR in MDA-PR-B+ cells. The mechanism of ARV action on PR-B activity was investigated by competitive binding assays, as well as by determination of PR phosphorylation levels. The effect of the GR on progestogen-induced PR-B activity in terms of potency, efficacy and biocharacter was investigated using promoter-reporter assays, real-time qPCR on select endogenous genes and efficacy on multiple genes in a PCR array. Using GR-specific siRNA knockdown in MDA-PR-B+ cells, the progestogen-induced PR responses were compared for higher and lower GR levels. The mechanism of the effect of the GR on PR activity was further investigated by co-immunoprecipitation studies and the degree of PR phosphorylation in the presence of higher and lower GR levels was also compared. Results show that in the presence of the progestogens investigated, in vitro biological responses via PR-B can vary significantly in biocharacter and absolute values for efficacies and potencies. Progestogen-specific responses were found on the same synthetic promoter, as well as on the same endogenous gene in the same cell. These progestogen-specific responses negatively correlated with progestogen-specific metabolism in U2OS cells. Furthermore, the progestogen-specific responses also varied in a gene- and model system-specific manner. The majority of the progestogeninduced responses via PR-B were significantly more efficacious, but less potent that the progestogen-induced responses via PR-A, highlighting the importance of the relative expression of PR-B vs PR-A protein levels in determining the resultant progestogen-specific response. It was shown for the first time that the ARVs, MVC and TDF activated PR-B transcription in the absence of progestogens to result in increased transcription in promoter-reporter assays and increased mRNA for endogenous genes. MVC and TDF exhibited no direct binding to PR-B; however, novel data from this thesis showed increased PR-B phosphorylation at Ser294 with TDF but not MVC. DPV activated two PR-regulated genes in the absence of progestogens and competed for binding of P4 to PR-B, while resulting in no effect on PR-B phosphorylation. Using GR-specific siRNA, it was determined by promoter-reporter assays that the presence of the GR had an inhibitory effect on PR-B efficacy. This surprising observation was supported by the global and promoter-specific gene expression changes observed for some genes using a PCR array with and without GR knockdown. The mechanism by which the GR affects the PR-B activity was determined to be most likely by association with PR-B in the same protein complex, probably resulting in a significant decrease in PR-B phosphorylation. Taken together, the in vitro differences between progestogen actions via the PR suggest that the absolute values of the progestogen-induced efficacies and potencies are likely to vary in vivo in a progestogen-, promoter-, model system- and isoformspecific manner. While obtaining such data in vivo is not possible, the in vitro data from the present study show proof-of-concept of potential significant cell-, gene- and progestogen-specific PR-B effects, as well as PR isoform-specific effects. Additionally, this study shows that potential novel off-target immunomodulatory effects of MVC, TDF and DPV occur in vitro and these are most likely mediated by different mechanisms of PR-B activation. Lastly, this study shows that in cells where both the GR and PR-B are co-expressed, the resultant PR response is likely to be inhibited on select genes as a result of reduced PR-B phosphorylation. The extent to which the presence of the GR affected the determination of progestogen-, model system-, promoter- and isoform-specific responses of progestogens via the PR in this study was not investigated for all models and genes, but is likely to be an unavoidable confounding factor. However, since all cells that express the PR also express the GR in vivo to the best of the author's knowledge, characterising PR activity in the absence of detectable GR expression is unlikely to be physiologically relevant. Collectively these data suggest that multiple factors influence PR activity and these need to be taken into account, especially given the treatments available and under investigation, which are designed to specifically target the PR.